The Bible in Arabic The Scriptures of the 'People of the Book' in the Language of Islam - Griffith, Sidney Harrison 1938- (Princeton Princeton University Press, 2013)
From the first centuries of Islam to well into the Middle Ages, Jews and Christians produced hundreds of manuscripts containing portions of the Bible in Arabic. Until recently, however, these translations remained largely neglected by Biblical scholars and historians. In telling the story of the Bible in Arabic, this book casts light on a crucial transition in the cultural and religious life of Jews and Christians in Arabic-speaking lands. In pre-Islamic times, Jewish and Christian scriptures circulated orally in the Arabic-speaking milieu. After the rise of Islam--and the Qur'an's a
Cover; Title; Copyright; Dedication; Contents; List of Illustrations; Preface; INTRODUCTION; CHAPTER I: The Bible in Pre-Islamic Arabia; CHAPTER II: The Bible in the Arabic Qur'ān; CHAPTER III: The Earliest Translations of the Bible into Arabic; CHAPTER IV: Christian Translations of the Bible into Arabic; CHAPTER V: Jewish Translations of the Bible into Arabic; CHAPTER VI: Muslims and the Bible in Arabic; CHAPTER VII: Intertwined Scriptures; Bibliography; Index
Description based upon print version of record
Reproduktion
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Vertalingen; Islam -- Relations -- Christianity -- Congresses; Ubersetzung; Bijbel; Christianity and other religions -- Islam -- Congresses; Church History -- Arab countries -- Congresses; Arabisch; Bible. Arabic -- Versions -- History; Bible. Arabic -- Versions -- History -- Congresses; Muslims; Religion / History; Bible -- Arabic -- Versions -- History; Al-Andalus; Allusion; Alphonse Mingana; Anno Domini; Apocalypse of Peter; Apologetics; Arab Christians; Arabic alphabet; Arabic script; Arabic; Arabs; Bible translations; Bible; Biblical criticism; Book of Job; Caliphate; Cambridge University Press; Christian literature; Christian scripture; Christian theology; Christian tradition; Christian; Christianity and Judaism; Christianity; Christology; Church of the East; Classical Arabic; Copts; Crucifixion of Jesus; Diatessaron; Electronic books